Social policies or private solidarity? The equalizing role of migration and remittances in El Salvador - Carlos Acevedo; Maynor Cabrera (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper reviews the pattern of poverty rates and income inequality in El Salvador since the 1990s. It discusses some of the likely factors that explain the reduction in income inequality that has taken place in the country in the last decade, which paradoxically has coincided with the long period of economic stagnation that has followed dollarization since 2001. After examination of the available evidence, we conclude that this trend has been mainly due to the equalizing effect of migration and remittances (that is, a 'private safety net' built around solidarity within families) rather than the distributive effect of public social expenditure or other public policies.
Keywords: D63; E24; I32; J61; 330; El Salvador; remittances; migration; inequality; poverty; labour market; Armut; Einkommensverteilung; Rücküberweisungen; El Salvador